Data for paper "Aerodrome Situational Awareness of Unmanned Aircraft: An Integrated Self-Learning Approach with Bayesian Network Semantic Segmentation" - Bowen Lu; Matthew Coombes; Baibing Li; Wen-Hua Chen (2018)
The .rar file contains:1. GPS location data CSV2. Processed input videos to algorithm3. Output videos to algorithm4. Code to run algorithm